SPECIFIC ASPECTS OF STUDYING THE CREATION OF SAMUYIL MARSHAK - Makhmud ABDULLAEV (Scholar Express Journal, 2023)
In extracurricular lessons, it is necessary to first introduce children to the work of Samuyil Yakovlevich Marshak, and the teacher should tell the students about the life and work of this artist.
Keywords: Literary; night; student; ability